"I don't bang: I'm just a Blood": Situating gang identities in their proper place. (February 2021) - Lopez-Aguado, Patrick; Walker, Michael Lawrence
In this article we offer a theoretical framework for conceptualizing the relationship between gang identification, place, and identity saliency. In our interviews with current and former street gang members, participants consistently described gangs as neighborhood-based entities, but also couched these local identities within much broader Crip or Blood affiliations. These amount to multiple, simultaneously claimed identities. However, we show that not all identities are equal—that as a social geographic area increases, identities become more diffuse and less salient, territorial, or "gang-like", resulting instead in expansive, symbolic "umbrella identities" that cover several distinct places and gangs. These umbrella identities proved quite fluid, such that Crip and Blood affiliations had little relationship to one's gang identity and even produced some gangs with mixed Blood and Crip memberships.